Case Study Of The Causes Of The Accident Of The People's Shipping Ship Km Reski In The Waters Of Balang Caddi Island-Pangkajene Islands - Asri, Haerani; Nurwahidah, Nurwahidah; Susanti, Eva; Tona, Tasdik; Rachman, Subehana; Umasangadji, Fahmi (Departemen Teknik Kelautan Universitas Hasanuddin, 2024)
This research aims to determine the causes of the KM Reski People's Shipping Ship Accident in the waters of Balang Caddi Island-Pangkajene Islands. The data analysis method in this research is quantitative and qualitative description. In this research, the sample selection was carried out using purposive sampling, namely a sampling technique with certain considerations, in this case all those on board the people's shipping vessels in the waters of Balang Caddi Island-Pangkajene Islands. The data collection method used in this research is an interview, which is unstructured but at a minimum the researcher uses a plan of questions to be asked as an interview guide. Based on the results of interviews by 35 respondents, in this case passengers, ship owners and captains, by asking questions with three indicators, namely related to safety equipment, decisions on safety regulations, and education and knowledge of human resources, it turns out that after interviews were conducted and analyzed, these three indicators were said to be low/fair, this is said to be the result of the KM Reski ship accident in the waters of Balang Caddi Island, due to lack of knowledge and lack of availability of safety equipment. .